THU0411 Utility of ultrasound scores in assessment enthesitis on anti-TNF therapy of spondyloarthritis patients. (23rd January 2014) - Istrate, A.M.; de Miguel, E.; Felea, I.; Caracuel Ruíz, M.Ά.; Collantes-Estevéz, E.
Abstract : Background: Entheses affectation is the hallmark lesions in ankylosis spondylitis (AS). In front of the cardinal role of enthesis inflammation on SpA is the finding that clinical examination lacks sensitivity and specificity, as has been demonstrated by several studies comparing clinical evaluations with new imaging techniques as ultrasound (US). Objectives: To explore the utility and concurrent validity of enthesis US MASEI score in SpA patients with anti-TNF therapy. Methods: Thirty four patients with AS, fulfilling modified New York criteria in treatment with biologic therapy were enrolled. All patients underwent a clinical evaluation, following up: the AS-specific scores Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankyosing Spondylitis Functional Index (BASFI) and the enthesitis-specific scores MASES. Laboratory data included inflammatory parameters (ESR and CRP). Ultrasound evaluation.The MASEI US score was applied to every patient. The MASEI score is a weighted score previously calculated by logistic regression that overestimates the score of three elemental lesions: calcification (0-3), Doppler (0 or 3), erosion (0 or 3), while scoring tendon structure, tendon thickness and bursa is either a 0 or 1. The score range is between 0 and 136. Results: Thierty four patients, 21 (61%) men and 13 (39%) women with a mean age of 44.5±9.5 (range, 32-59) were enrolled. The patients had a mean of disease duration of 10.36±6.86 years and a mean duration of biologic therapy was 50±31.5 months. Laboratory tests indicated high level of ESR and CRP were in 10 (31%) patients: mean ESR was 16.38±18.9 (range, 2-100) and mean serum CRP was 9.92±20.09 (range, 1-84.3). Thierty two patients (93.7%) were HLA-B27 positive and two patients (6.2%) was negative. BASDAI score was >4) in 38, 2% of patients and MASES score >0 at 22 patients (64, 7%) at the moment of the US examination. Conclusions: All ultrasound elemental lesions had lower scores in BASDAI responders but only Doppler signal was a significant difference and completely disappear in anti-TNF responder SpA patients. If this is confirmed by others Doppler signal can became and useful measure to asses enthesitis in SpA. Disclosure of Interest: None Declared